Examining the gender digital divide: A case study from rural Bangladesh - Sufian, Farha D.; Nico, Gianluigi; Azzarri, Carlo (International Food Policy Research Institute, 2023)
Women farmers in Bangladesh face several challenges when it comes to accessing technology and information, and this limits their ability to improve their agricultural productivity and enhance their livelihoods. The gendered digital divide is a significant contributor to inequities in agriculture and has important implications for women’s empowerment. Lack of access to information affects their ability to make informed decisions, access markets, and secure their rights. This policy note summarizes research designed to identify the barriers female farmers in Bangladesh face in accessing technology and information so that future policies and initiatives can address these challenges and, in so doing, promote gender equality and the empowerment of rural women.